Robson Ten Group Classification System Applied to Women with Severe Maternal Morbidity. Issue 1 (March 2015) - Ferreira, Elton Carlos; Costa, Maria Laura; Cecatti, José Guilherme; Haddad, Samira M.; Parpinelli, Mary Angela; Robson, Michael S.; the Brazilian Network for Surveillance of Severe Maternal Morbidity Study Group
Abstract Objective To evaluate the distribution of women with severe maternal morbidity according to Robson Ten Group Classification System (RTGCS). Methods Secondary analysis of a multicenter cross‐sectional study in 27 obstetric units in Brazil, using RTGCS. Cases were classified into potentially life‐threatening condition or a maternal near miss or death, according to severity. Certain groups were subdivided for further analysis. Cesarean delivery (CD) rates were reported. Results Among 7, 247 women with severe maternal morbidity, 73.2 percent underwent CD. Group 10 (single, cephalic, preterm) was the most prevalent (33.9%). Groups mostly associated with a severe maternal outcome were: 7 (multiparous, breech), 9 (all abnormal lies, single, term), 8 (all multiple), and 10. Groups 1 (nulliparous, single, cephalic, term, spontaneous) and 3 (multiparous, single, cephalic, term, spontaneous) were associated with better maternal outcome. Group 3 had one severe maternal morbidity to 29 cases of potentially life‐threatening, but the ratio was 1:10 for women undergoing CD, indicating a worse outcome. Group 4a (multiparous, no previous CD, single, cephalic, term, induced labor) had a better maternal outcome than those delivered by CD before labor (group 4b). Hypertension was the most common condition of severity. Conclusions The RTGCS was useful to consider severe maternal morbidity, showing groups with higher CD rates and worse maternal outcomes.